Attitudes Towards AI in Healthcare Among High School Students and Healthcare Professionals in Toronto - Sushrut Lamsal (The Young Researcher)
Discussions about artificial intelligence (AI) in healthcare are becoming increasingly prevalent, given the growing influence and developments of AI. Furthermore, the scale of AI’s influence renders it important to understand the views of both younger and older generations, as they represent the future and current attitudes of recipients and leaders of healthcare. This study explores the attitudes towards AI in healthcare among high school students – an underrepresented demographic in the literature – and healthcare professionals in Toronto, Ontario. Using an explanatory sequential mixed-methods approach, a survey was conducted using a 5-point Likert scale to assess participants’ (n = 68) overall views and establish broad trends across four domains: confidence, concerns, ethical and regulatory concerns, and practical applications. Optional, structured interviews were then conducted with willing participants (n = 15) to provide context to survey responses. This study benefits policymakers and governments in ensuring that AI development in healthcare aligns with public expectations.